Situation Report: Poland, 25 May 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Political Prisoners in Barczewo End Hunger Strike / by Janusz Bugajski Polish-Soviet Economic Agreement / by Marian Barczewski The Sovietization of Poland Gathers Momentum / by Janusz Bugajski Taming the Intellectuals: The Scientists / by Ewa Celt Polish Automobile Industry Going Downhill / by Janusz Bugajski Sundry Items